Tecnobrega: os contrastes de uma identidade cultural para o jovem periférico - RIBEIRO, Lucilene do Nascimento (2019)
The Technobrega is a dancing rhythm from Pará that mixes elements of the local culture with electronic beats, much appreciated by young people, especially those who live in peripheries. Because it is present in the leisure spaces, residences and still be a generator of youth and adults, it is important to investigate how the requirements for culture and life of the peripheral young. With this, we propose new classes in the field of dance in Physical Education class, emphasizing as a way to involve the student, not only in dance, but in also fostering cultural in class. The research was done on the qualitative type, a review of the literature on the subject and a qualitative survey on the Tecnobrega with the agents related to the rhythm and a Physical Education teacher. Research theory and respondents' assertions point to the cultural potential of implementing the rhythm, for reflection on their culture and understanding of local culture. Therefore, being a Physical Education class, a human construction site, such moments can be used to include the rhythm of the culture of Pará.